Terms-of-Trade Cycles and External Adjustment - Adler, Gustavo (IMF Working Papers; Working Paper ;, 2017)
We study the process of external adjustment to large terms-of-trade level shifts-identified with a Markov-switching approach-for a large set of countries during the period 1960-2015. We find that adjustment to these shocks is relatively fast. Current accounts experience, on average, a contemporaneous variation of only about 1\2 of the magnitude of the price shock-indicating a significant volume offset-and a full adjustment within 3-4 years. Dynamics are largely symmetric for terms-of-trade booms and busts, as well as for advanced and emerging market economies. External adjustment is driven primarily by offsetting shifts in domestic demand, as opposed to variations in output (also reflected in the response of import rather than export volumes), indicating a strong income channel at play. Exchange rate flexibility appears to have played an important buffering role during booms, but less so during busts; while international reserve holdings have been a key tool for smoothing the adjustment process.